The transcription factor, the Cdk, its cyclin and their regulator: directing the transcriptional response to a nutritional signal. - Hirst, K; Fisher, F; McAndrew, P; Goding, C (1994)
The Pho80-Pho85 cyclin-cdk complex prevents transcription of PHO5 by inhibiting the ability of the basic-helix-loop-helix transcription factor Pho4 to activate transcription in response to high phosphate conditions. In low phosphate the Pho80-Pho85 complex is inactivated and Pho4 is then able to activate the acid phosphatase gene PHO5. We show here that Pho4 and the homeobox protein Pho2 interact in vivo and act cooperatively to activate the PHO5 UAS, with interaction being regulated by the phosphate switch. In addition, we also demonstrate that an additional factor, Pho81, interacts in high phosphate with both the Pho80 cyclin and with Pho4. In low phosphate, Pho80 and Pho81 dissociate from Pho4, but retain the ability to interact with each other. The evidence presented here supports the idea that Pho81 acts as a phosphate-sensitive trigger that regulates the ability of the Pho80-Pho85 cyclin-cdk complex to bind Pho4, while DNA binding by Pho4 is dependent on the phosphate-sensitive interaction with Pho2.